The Potency of Citrus aurantiifolia Swingle and Sea Salt Solution as a Cleansing Agent for Edible Bird’s Nests - Ningrum, Siti Gusti; Candra, Adhitya Yoppy Ro; Wardhani, Hana Cipka Pramuda (UI Scholars Hub, 2023)
The present study aimed to evaluate the potency of Citrus aurantiifolia Swingle and sea salt solution as a promising cleansing agent for edible bird’s nests (EBNs). Ascorbic acid, sodium, and chloride analyses of the C. aurantiifolia Swingle and sea salt solution were conducted using HPLC, ICP-OES, and titrimetry, respectively. The characteristics of physical samples and hydrogen peroxide detection were examined in this study. The reduction activity of the Citrus aurantiifolia Swingle and sea salt solution on the nitrite of 120 white EBNs was studied. This nitrite reduction activity was compared with the available method (standard), drinking water method, 6% C. aurantiifolia Swingle extraction method, and sea salt water. An organoleptic test was performed by three trained panelists to determine the color of the samples before and after treatments. The results showed that the C. aurantiifolia Swingle and sea salt solution contained 0.27 mg/100 mL of ascorbic acid, 76370.93 mg/L of sodium, and 7555.61 mg/100 mL of chloride. In comparison results, the C. aurantiifolia Swingle and sea salt solution can reduce nitrite levels up to 86%, remove hydrogen peroxide, and improve the natural color of EBNs. The present study provides the first potential future cleansing agent for EBNs.